Laser beam welded sandwich structures with hollow sphere core. Issue 5 (29th May 2013) - Riegel, H.; Merkel, M.; Öchsner, A.; Araújo, M.; Thiede, R.; Fruhstuck, J.
Abstract Metallic hollow sphere structures (MHSS) are advanced composite materials characterised by a high geometrical reproducibility with relatively constant mechanical and physical properties. The success of such new developed materials depends not only on the production itself. The techniques for further processing and joining are essential. Joining technologies like brazing or gas metal arc welding influence the hollow sphere structures bulk material with a considerable amount of heat. The laser beam welding is a highly efficient technique with a comparatively small heat input. The laser beam ensures only local heat influences and allows individual structures for specific sandwich geometries. The joining of blanks with hollow sphere structures expands the applications and possibilities for them. The challenge of welding hollow sphere structures, for example with blanks to a sandwich structure, lies in the low density of hollow spheres. The surface tension of the molten hollow sphere structures forces the melt to form droplets out of bulk material. The metallic hollow sphere structure vanishes. The missing material can be balanced by feeding massively a wire into the welding bath. However, the additional mass is not suitable for light weight constructions. A joint between the molten feeding wire and a hollow sphere can still not be ensured. Classical joining technologies with a big amount of heat would dissolve the complete hollow sphere structures and are not suitable. In this paper the mechanical properties of laser beam welded hollow sphere structures sandwich structures are presented. The welding was done by a CO2‐laser with a wave length of 10.6 μm and a maximum power of 1.5 kW. Different geometries of joints have been investigated. The specimens are tested for shear and bending strength. The strength of the weld lines depend on the density of the hollow sphere structures. Higher density raises the strength. Eigenfrequencies have been simulated by modal analysis. Results of simulated and measured values show comparable results, starting by 2 kHz for 1 mm thick blanks and 3 kHz for 2 mm blanks.